1-Chloro-n-alkanes: Potential mangrove and saltmarsh vegetation biomarkers. (May 2017) - Tulipani, Svenja; Schwark, Lorenz; Holman, Alex I.; Bush, Richard T.; Grice, Kliti
Highlights: Long-chain 1-chloro- n -alkanes were investigated as potential halophyte biomarkers. Distinct distributions in plant tissue were linked to other leaf-wax components. Chloro-alkane biosynthesis likely related to n -alkyl lipid formation pathways. δ 13 C values reported for the first time and consistent with such formation pathways. Previous reports in sediments suggest sufficient stability for biomarker application. Abstract: Chlorinated hydrocarbons with biological sources occur in high abundance and diversity in living organisms as well as in sedimentary environments. Although some of these compounds are potentially highly source-specific and sufficiently degradation-resistant, their capacity as sedimentary biomarkers remains under-investigated. Distinct series of long-chain 1-chloro- n -alkanes have previously been reported in three species of European saltmarsh vegetation; however, these compounds have never been further investigated in a more diverse plant population. Here we report the presence of similar series with a typical higher plant odd/even carbon number predominance in species of Australian mangrove and saltmarsh vegetation, including the black mangrove Lumnitzera racemosa, the grass Sporobolus virginicus and samphire, supporting the potential use of long-chain 1-chloro- n -alkanes as halophyte biomarkers. Based on carbon stable isotope values, which were reported here for the first time, and similarities in their distributions, we propose that the biosynthetic pathway of chloroalkanes is linked to that of other n -alkyl plant wax components.